A change in perspective - Teacher education as an open system - Christoph König; Regina H Mulder (EARLI, 2014)
Teacher education is the environment for the learning and instruction of prospective teachers. Its structure, components, and contents shape the development of relevant competences which enable prospective teachers to be effective in the classroom. But its relevance is questioned because respective research, characterised by inconclusive results, does not offer explanations about the reasons why certain teacher education programmes are more effective than others in the development of relevant competences. One reason for the lack of explanations can be found in the way research assesses the effectiveness of teacher education. This might be due to problems regarding the conceptualisations of teacher education, as well as to the inherent selection and non-random allocation problems in research on the relation between teacher education and student achievement. In this paper we respond to claims for an organisational perspective on teacher education and develop such a new perspective. Accordingly, we provide these claims with an adequate theoretical foundation and develop an organisational model of teacher education based on Open Systems Theory. Besides being one of the first integrative organisational models of teacher education, it is among the first models which illustrate the relations and interdependencies of systems, its different parts, and its different levels, and enables researchers to investigate these interdependencies. The development of this model is further based on an alteration of the input variables of the concept of teacher quality. Moreover, the model has consequences for the notion of teacher education effectiveness. We illustrate these changes, and discuss them and the model with respect to possible areas of further research.